Development of Chili Farming in Pojok Hamlet, Klitih Village - Muchamad faruq Almuzaqqi; Zulfikar (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
Chili farming is a type of agriculture that brings in a lot of money and helps farmers earn more income. Pojok Hamlet, Klitih Village, Plandaan District, Jombang Regency is a place where the majority of the people are involved in farming chilies. But farmers still have many issues that impact how much they can produce and how well their businesses run. This research looks into how productive chili farming is and finds out the challenges that farmers face. The research used a qualitative descriptive approach. The research area was chosen on purpose, and the people involved were selected through a snowball sampling method, which included 26 chili farmers. The main information came from interviews and watching things happen on-site, and the additional information was gathered from books and other places where similar information is kept. The data analysis involved a descriptive analysis that included looking at farm costs, revenues, incomes, and the return to cost ratio. The results indicate that growing chili in Pojok Hamlet is a good financial decision because the return on capital is more than one. Productivity depends on the size of the land, the types of seeds used, and how the production is managed. Main problems are changing prices, harm from bugs and illnesses, weather that isn't reliable, and not enough money. Keywords: chili farming; productivity; R/C ratio; agribusiness; farm feasibility